2020
DOI: 10.13189/ujar.2020.080403
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and Temperature Predictions: Implications for Rice Production in the Lower River Region of The Gambia

Abstract: Climate change impacts have been the major subject of discussion for scientists from different fields of study, including the agriculture sector. This study investigates the effects and implications of future climate change on rice production in the Lower River Region of The Gambia. The study seeks the following specific objectives: i) Analyse temperature and rainfall trends over Lower River Region; ii) Determine the relationship between temperature, rainfalls and rice production in the study area; and iii) Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…also confirms that crops in Senegal, South-West Mali, Burkina Faso, and South-West Niger are more responsive to climate stresses and impact negatively on crop production in the four regions. The study byBagbohouna et al (2020) revealed that an increase in maximum temperature (Tmax) and a variation in minimum temperature (Tmin) have a negative impact on crop yields Grüter et al (2022). confirm that climate change in the form of high temperatures and flooding impedes the growth of coffee, cashew, and avocado in Guinea Bissau.…”
mentioning
confidence: 86%
“…also confirms that crops in Senegal, South-West Mali, Burkina Faso, and South-West Niger are more responsive to climate stresses and impact negatively on crop production in the four regions. The study byBagbohouna et al (2020) revealed that an increase in maximum temperature (Tmax) and a variation in minimum temperature (Tmin) have a negative impact on crop yields Grüter et al (2022). confirm that climate change in the form of high temperatures and flooding impedes the growth of coffee, cashew, and avocado in Guinea Bissau.…”
mentioning
confidence: 86%